2018
DOI: 10.3389/fmicb.2018.03019
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Protein Secretion in Streptomyces Using Fluorescent Proteins

Abstract: Fluorescent proteins are a major cell biology tool to analyze protein sub-cellular topology. Here we have applied this technology to study protein secretion in the Gram-positive bacterium Streptomyces lividans TK24, a widely used host for heterologous protein secretion biotechnology. Green and monomeric red fluorescent proteins were fused behind Sec (SPSec) or Tat (SPTat) signal peptides to direct them through the respective export pathway. Significant secretion of fluorescent eGFP and mRFP was observed exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 78 publications
2
36
0
1
Order By: Relevance
“…It has been shown that poor cell growth can be associated with increased secretion of endogenous and heterologous products [3, 34], and that secretion cannot easily be coupled to other objectives [3, 18, 3335]. Protein secretion poses a well-known additional problem since conflicting objectives lead to a controversial DFBA solution: if priority is given to growth, the cell will limit secretion to save resources, whereas if priority is given to secretion, it will proceed at the expense of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that poor cell growth can be associated with increased secretion of endogenous and heterologous products [3, 34], and that secretion cannot easily be coupled to other objectives [3, 18, 3335]. Protein secretion poses a well-known additional problem since conflicting objectives lead to a controversial DFBA solution: if priority is given to growth, the cell will limit secretion to save resources, whereas if priority is given to secretion, it will proceed at the expense of growth.…”
Section: Discussionmentioning
confidence: 99%
“…Application of feature extraction methods identified relevant associations with H 2 O 2 (likely as an indicator of oxidative stress, which is associated to the onset of the stationary phase, to the decline in α-amylase secretion and to the surge in agarase production), L-alanine, mannitol, other amino acids and, surprisingly, four metallic ions (Mo 2+ , Ni 2+ , Cu 2+ , Co 2+ ) whose association with secretion had never been noticed before. Coincidentally, a recent study [34] reported that S. lividans grown in minimal medium (MM) had a low yield in mRFP protein secretion, whereas growth in CM/glucose had a high yield, on the opposite side of the spectrum, only paralleled by NB medium (a rich medium with peptic digest of animal tissue and beef extract). The only qualitative differences between MM and CM/glucose are the presence in CM/glucose of CuSO 4 and CoCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In the Sec secretion system, SecA converts ATP energy to drive the translocation of preproteins across the SecY, SecE and SecG channel in the bacterial cytoplasmic membrane. Exported preproteins containing N-terminal signal sequences transit the cytoplasm in non-folded states, with or without bound chaperones (Kusters and Driessen, 2011;Chatzi et al, 2014;Busche et al, 2018;Hamed et al, 2018b).…”
Section: Finding New Antibiotics Against New Bacterial Target Proteinmentioning
confidence: 99%
“…In the Sec secretion system, SecA converts ATP energy to drive the translocation of preproteins across the SecY, SecE and SecG channel in the bacterial cytoplasmic membrane. Exported preproteins containing M -terminal signal sequences transit the cytoplasm in non-folded states, with or without bound chaperones (Kusters and Driessen, 2011; Chatzi et al, 2014; Busche et al, 2018; Hamed et al, 2018b). After preprotein translocation into the periplasm (Gram − ) or extracellular space (Gram + ), signal sequences are removed by membrane-embedded signal peptidases and exported proteins acquire their native structures or are further trafficked (Kusters and Driessen, 2011; Hamed et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to Sec, the Tat pathway translocates proteins that are already intracellularly folded, possibly containing cofactors. Tat signal peptides N-region contains a conserved S/T-R-R-x-FLK motif and their H-region is less hydrophobic than the one from its Sec homologue (Hamed et al, 2018). The Tat translocon consists three integral membrane proteins: TatA proteins family, that form the translocation channel; and TatB and TatC, that assemble to form a multivalent receptor complex to which Tat signal peptides bind (Fig.…”
Section: Twin-arginine Translocationmentioning
confidence: 99%